Financial Distress Ditinjau Dari Leverage, Intangible Asset, Tangible Asset dan Ukuran Perusahaan - Lidia Desiana; Muhammad Junestrada Diem (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2021)
This study examines the Effect of Leverage, Intangible Assets, Tangible Assets and Company Size on Prediction of Financial Distress in Companies Listed in the Jakarta Islamic Index for the 2014-2019 Period. The independent variables in this research are Leverage, Intangible assets, Tangible Assets and Company Size, while the variable is Financial Distress which is a description of the company's financial failure as measured by the Springate model or better known as the S-Score. The population in this study are companies listed at JII for the period 2014-2019. Sampling technique with purposive sampling method. A total of 14 companies for 6 years. Logistic regression analysis using IBM SPSS. The leverage variable with a value of -0.007 and a significance value of 0.109, that is > 0.05, means that leverage has no effect on financial distress. The intangible asset variable has a value of 0.053 with a significance value of 0.888 that > ​​0.05 then intangible assets have no effect on financial distress. The tangible asset variable has a value of -1.506 and a significance value of 0.002 that <0.05, then tangible assets have an effect on financial distress. The size variable has a value of -1.453 and a significance value of 0.007 that < from a significance level of 0.05, the size has an effect on financial distress. The conclusion shows that only tangible assets and size variables have an effect on financial distress, while leverage and intangible assets have no effect on financial distress.